The Long-Term Effects of Parental Absence as Migrant Workers on the Psychosocial Development and Education of Young Children: A Literature Review in Indramayu Regency: Indonesia - Mulyani, Atri; Zevender, Poy Saefullah; Kholish, Faiq Khafidz; Liandy, Santi; Aziz, Gil (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The aim of this study is to examine how the absence of parents as migrant workers impacts the psychosocial development of young children. The research focuses on various components of child psychosocial development, such as emotional attachment, moral development, language skills, and social interaction with peers. To achieve this, a literature review was conducted by gathering information from various sources, including articles, journals, and previous studies related to the topic. The results show that the absence of parents working as migrants can affect a child's psychosocial development, including their ability to interact socially, self-confidence, and independence. Children raised by caregivers or other family members tend to feel emotionally insecure and face difficulties in forming stable relationships. Furthermore, the lack of direct parental supervision can hinder the development of moral and language skills. This study also emphasizes the importance of caregivers or substitute figures in supporting the psychosocial development of children during the early stages of their lives. The findings are expected to provide insights for child-rearing policies and support efforts to improve the quality of child care for children of migrant workers.